Development of 3D models and animations for LED cube - Au, Benny Kai Jie (Nanyang Technological University, 2020)
When people first envision the thought of building a LED cube, numerous ways of i mplementation can be found online. Ranging from simple 4 x 4 x 4 LED cubes to 8x8x8 LED cubes that can take in user commands, to full size 32x32x32 LED cubes meant for huge indoor displays. This project int en d s to utilize LED cubes to help with the understa nding of complex physics concepts, namely vectors and ele ctromagnetic waves. By using the LED cube to display 3D models of electromagnetic waves, allowing users to look at the waves from different angles o n the cube and hopefully assist them in comprehendi ng the concepts better. This project aims to utilize the capabilities of a commercially available LED cube to implement the functions that are required to display waveforms. This report will explore the various functions and features of the commercial prod uct and evaluate its usefulness.